Experimental Research on NOx Emission Characteristics During Coal Combustion in the Stoker-fired Boiler. (March 2019) - Guo, Xinwei; Zhang, Zhongxiao; Yu, Juan; Zhang, Jian; Bi, Degui; Dong, Jiancong; Bai, Hao; Fan, Junjie
Abstract: In this paper, the combustion stability and nitrogen oxides (NOx) emissions test were made in two coal-fired chain grate boilers with hot water supplies of 29MW and 46MW. The investigations aim to clarify the key characteristics of NOx emission, e.g.instability of NOx emission, temperature and gaseous components profiles and the unsteady variation of NOx emission with power level changing. Main conclusions include: 1) In the process of stable combustion, NOx emissions still have±5% fluctuations, it is not stable. 2) The furnace temperature distribution show double temperature peaks. One peak ( 1500°C) is located on the burning solid-fuel surface on the chain grate, and the other ( 1050°C) is 5.6m above the arch. 3) With increasing the thermal power, NOx emission shows a dramatic increase, higher around 1.25 times, as due to the rapid adjustment of coal feeding in grate furnace. Those above show the NOx control difficulty and the proper injector location of SNCR (selective non-catalytic reaction), which is key data collected for further NOx reduction retrofits.